Association of Chinese herbal medicine use with the depression risk among the long-term breast cancer survivors: A longitudinal follow-up study - Yang, Shu-Yi; Livneh, Hanoch; Jhang, Jing-Siang; Yen, Shu-Wen; Huang, Hua-Lung; Chan, Michael W. Y.; Lu, Ming-Chi; Yeh, Chia-Chou; Wei, Chang-Kuo; Tsai, Tzung-Yi (Frontiers in Psychology, 2022)
Background: Breast cancer patients are at elevated risk of depression during treatment, thus provoking the chance of poor clinical outcomes. This retrospective cohort study aimed to investigate whether integrating Chinese herbal medicines (CHM) into conventional cancer therapy could decrease the risk of depression in the long-term breast cancer survivors. Methods: A cohort of patients aged 20–70 years and with newly diagnosed breast cancer during 2000–2008 was identified from a nationwide claims database. In this study, we focused solely on survivors of breast cancer at least one year after diagnosis. After one-to-one matching for age, sex, and baseline comorbidities, breast cancer patients who received (n = 1450) and did not receive (n = 1450) CHM treatment were enrolled. The incidence rate and hazard ratio (HR) for depression between the two groups was estimated at the end of 2012. A Cox proportional hazard model was constructed to examine the impact of the CHM use on the risk of depression. Results: During the study period, the incidence rate of depression was significantly lower in the treated cohort than in the untreated cohort (8.57 compared with 11.01 per 1000 person-years), and the adjusted HR remained significant at 0.74 (95% CI 0.58 to 0.94) in a Cox proportional hazards regression model. The corresponding risk further decreasing to 43% among those using CHM for more than one year. Conclusion: Finding from this investigation indicated that the lower risk of depression observed in breast cancer patients treated with CHM, suggesting that CHM treatment should be considered for disease management towards breast cancer. Yet, the optimal administered dose should be determined in further clinical trials.